Semantic Architecture at Masjid Jami Adji Amir Hasanoeddin in Kutai Kartanegara Regency - Arsita*, Ema Dwi; Titisari, Ema Yunita; Asikin, Damayanti (Universitas Syiah Kuala, 2023)
The existence of the Jami Adji Amir Hasanoeddin mosque is a symbol of the progress of the Islamic religion in Kutai Kartanegara. The mosque is also a landmark of urban area identity and has ideology, concepts, history, culture, forms and acculturation that describe the identity of a society. An architecture with an identity needs to have a sense and concept that truly represents the built space in accordance with the culture and ideology of the community, so there is a need for research on the architectural semantics of the Jami Adji Amir Hasanoeddin mosque. The research method uses qualitative research with a descriptive approach using observations and interviews related to architectural semantics in mosques. The results of the research include position, shape, size, ornamental patterns and construction, it was found that Javanese, Middle Eastern, Kutai and Malay styles as well as connotative meanings related to the beliefs of the Kutai people